2010
DOI: 10.1158/1535-7163.mct-09-0679
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Dynamics, Mitotic Arrest, and Apoptosis: Drug-Induced Differential Effects of βIII-Tubulin

Abstract: Overexpression of βIII-tubulin is associated with resistance to tubulin-binding agents (TBA) in a range of tumor types. We previously showed that small interfering RNA silencing of βIII-tubulin expression hypersensitized non-small cell lung cancer cells to TBAs. To determine whether βIII-tubulin mediates its effect on drug-induced mitotic arrest and cell death by differentially regulating microtubule behavior, the effects of βIII-tubulin knockdown on microtubule dynamics were analyzed in H460 non-small cell lu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 14 publications
(25 reference statements)
8
92
2
1
Order By: Relevance
“…Given the importance of MTs in cell division and the widely accepted concept that cancer cells divide more rapidly than normal cells, it has been generally assumed that MTAs mediate cytotoxicity by interfering with mitosis (1, 2). Elegant in vitro and preclinical data have demonstrated time and again that MTAs lead to mitotic arrest and in turn cell death (5,(7)(8)(9)(10)(11)(12). Arrest in mitosis as the mechanism that leads to cell death is possible in these preclinical models because their doubling times range from a few hours to at most a few days, and even brief drug exposures are likely to encounter a substantial fraction of cells traversing through mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of MTs in cell division and the widely accepted concept that cancer cells divide more rapidly than normal cells, it has been generally assumed that MTAs mediate cytotoxicity by interfering with mitosis (1, 2). Elegant in vitro and preclinical data have demonstrated time and again that MTAs lead to mitotic arrest and in turn cell death (5,(7)(8)(9)(10)(11)(12). Arrest in mitosis as the mechanism that leads to cell death is possible in these preclinical models because their doubling times range from a few hours to at most a few days, and even brief drug exposures are likely to encounter a substantial fraction of cells traversing through mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Because the primary effect of taxane is to bind microtubules, thereby enhancing the microtubule polymerization and decreasing microtubule dynamicity, it has been suggested that βIII-tubulin-containing microtubules are more prone to overcome the suppressive effects of taxanes on microtubule dynamics. Although it should be noted that all the above studies (12,13,42) have focused on the assembly of purified microtubules in cell-free systems and therefore remain controversial given contradictory reports obtained in intact cells, and hence more biologically relevant, that βIII-tubulin did not intrinsically affect microtubule dynamic, at least in some instances (38,43). Interestingly, in these last studies, the effects of paclitaxel on microtubule dynamics were altered, suggesting a role for βIII-tubulin in drugmicrotubule interactions.…”
Section: Discussionmentioning
confidence: 99%
“…H460 and A549 NSCLC cells were obtained from ATTC and grown as described (8)(9)(10). Upon receipt from ATCC, cell master stocks were prepared and cells for experiments were passaged for less than 6 months.…”
Section: Cell Culturementioning
confidence: 99%
“…Clinical studies show that high bIII-tubulin expression correlates with chemoresistance and poor survival in different tumor types, including breast, ovarian, gastric, and NSCLC (5,6). Previously, we demonstrated a functional role for bIIItubulin in regulating chemosensitivity in NSCLC using RNA interference to silence bIII-tubulin expression in NSCLC cells (7)(8)(9)(10). Knockdown of bIII-tubulin increased sensitivity via an increase in apoptosis to chemotherapeutic agents both in vitro and in vivo (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation